Benchmarking Marine Energy Technologies Through LCA: Offshore Floating Wind Farms in the Mediterranean - Pulselli, Riccardo Maria; Maccanti, Matteo; Bruno, Morena; Sabbetta, Alessio; Neri, Elena; Patrizi, Nicoletta; Bastianoni, Simone (Frontiers in Energy Research, 2022)
Floating wind turbines are a valid option for offshore wind farms in the Mediterranean, where the sea-floor falls off rapidly with distance from the coastline. The present study concerns a Life Cycle Assessment of the environmental performance of two types of floating wind turbine. Greenhouse gas emissions of two standard models (raft-buoy and spar-buoy, 154 m rotor diameter, 6 MW installed power) were estimated in terms of Global Warming Potential (t CO2eq) with the aim of determining a benchmark for evaluating the performance of similar offshore wind farms. Thus, the aim of the paper was to create a benchmark for the design of innovative technologies, such as those developed by specialist companies, and to verify the validity of new designs and technologies in terms of avoided greenhouse gas emissions. The results show that the Carbon Intensity of Electricity of a single floating wind turbine varies in the range 26-79 g CO2eq·kWh-1, averaging 49 g CO2eq·kWh-1, in line with other studies of offshore wind turbines and other renewable energy sources (such as onshore wind and photovoltaic). Extension of our study to the whole life cycle, including manufacturing, assembly and installation, maintenance and material replacement and a hypothetical decommissioning and end-of-life, showed that wind farms are among the most promising marine renewable energy technologies for the Mediterranean.